A bibliometric analysis of the current state of research on family interventions for ASD - Meng, Xuhui; Zhou, Xue; Luo, Jiahui; Li, Jiaxia; Zhou, Li; Zhang, Yuhan (Frontiers in Psychiatry, 2025)
In recent years, family intervention has become a hot research direction in the field of autism spectrum disorder (ASD) treatment. A large amount of research literature shows that family intervention is effective in ASD rehabilitation. Still, the concept of family intervention is vaguely defined, and there is a lack of descriptions of specific intervention programs and treatment pathways and a diversity of intervention programs have been reported. In this study, we conducted an econometric analysis of the literature on family intervention for ASD to clarify the concept of family intervention and to analyze and explore the research hotspots, effective family intervention models for ASD, intervention techniques, and possible future research directions in this field.MethodsA metrological analysis of the literature related to ASD family interventions on the Web of Science from 1987 to 2024 was conducted using CiteSpace software to map the network of countries/institutions, journals, authors, co-cited literature, and keywords in the field. The results were visualized and analyzed.ResultsA total of 1,891 documents were retrieved. The United States (1,028) led in the number and relevance of publications, followed by Canada (254) and Australia (209). The trend of publications was upward. Baranek was the most published author (19) and the University of California System was the most published university. Developed countries dominate the research. According to the timeline graph, it can be learned that the current research hotspots in this field are mostly focused on early intervention in family-based, psychological stress in parents of children with autism.ConclusionThis visual analysis identifies the most influential institutions and countries, as well as cited journals and authors in the field of family therapy autism research. The direction of research in family therapy for autism should be to find effective treatments for autism based on the home environment, and currently, the most prominent family therapy for autism is telemedicine and parent-mediated intervention. The future direction of this research area could be taken by artificial intelligence techniques specifically applied to children with autism in a computer context.